2013
DOI: 10.1111/jam.12126
|View full text |Cite
|
Sign up to set email alerts
|

Production of aroma compounds by cryotolerantSaccharomycesspecies and hybrids at low and moderate fermentation temperatures

Abstract: Aim: Among the most important factors influencing wine quality are yeast strains and fermentation temperature. Fermentation at low temperature is presently used in winemaking to improve both aroma formation and retention. In this study, we have analysed the oenological characteristics of Tempranillo wines produced at 12 and 28°C by different Saccharomyces species and hybrids. Methods and Results: Low temperature had a strong influence on yeasts fermentation kinetics, increasing fermentation times to more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 44 publications
(42 reference statements)
9
98
4
Order By: Relevance
“…In contrast to our studies, for which a transient temperature decrease was applied, other studies have compared the impact of yeast fermentation temperature at 25 to 28°C and 12 to 15°C on the levels of volatile aroma compounds (Molina et al, 2007;Beltran et al, 2008;Gamero et al, 2013). The reduction in the yeast fermentation temperature had a major impact on the levels of volatile aroma compounds produced, and the levels produced varied between yeast strains.…”
Section: Figurecontrasting
confidence: 44%
See 3 more Smart Citations
“…In contrast to our studies, for which a transient temperature decrease was applied, other studies have compared the impact of yeast fermentation temperature at 25 to 28°C and 12 to 15°C on the levels of volatile aroma compounds (Molina et al, 2007;Beltran et al, 2008;Gamero et al, 2013). The reduction in the yeast fermentation temperature had a major impact on the levels of volatile aroma compounds produced, and the levels produced varied between yeast strains.…”
Section: Figurecontrasting
confidence: 44%
“…Fermentation at higher temperature (28°C) is reported to yield greater concentrations of higher alcohols that give flowery aromas to wine (Molina et al, 2007). On the other hand, Gamero et al (2013) found that the higher alcohol concentrations produced by 13 wine yeasts after fermentation at 28° compared to 12°C varied considerably between strains, pointing to an inconsistent response pattern to increased temperature.…”
Section: Figurementioning
confidence: 52%
See 2 more Smart Citations
“…The spectrum of compounds produced was shown to be temperature dependent 25 , such that non-hybrid strains were thought to have a more appealing aroma profile at higher temperatures. Analysis of regulation of aroma production indicated that the hybrids have unique regulatory mechanisms for aroma production not easily predicted from the parental strains 26 .…”
Section: Key Themesmentioning
confidence: 99%